Takim mnie zapamiętajcie - Łukasiewicz, Jacek (1934-2021).; Różewicz, Tadeusz (1921-2014). (2015)
Recenzja książki: Wiersze przeczytane / Tadeusz Różewicz. Wrocław, 2014.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.